Constitutive modeling and implicit-explicit predictive analysis of reinforced concrete structures - Alkaraghouli, Faris H (ProQuest Dissertations & Theses, 1997)
The importance and necessity of developing a general algorithm to realistically predict the response of concrete structures under general loading conditions were stated. The complexities involved in the problem were also pointed out. Generic flow charts are presented to qualitatively describe the steps involved in progressively analyzing such a continuum under both static and dynamic loading. These steps indicated that a vast amount of knowledge, involving structural mechanics, constitutive modeling, fracture and post fracture criteria, finite element and time integration methods, and computer implementation and coding, needs to be combined to devise a general solution algorithm. A detailed literature review concerning numerical integration methods was presented. The implicit-explicit direct integration method was examined. It is this mixed method that is implemented into the computer code. We reviewed the classical plasticity theory, on which the most commonly used constitutive models for concrete are based. This was followed by a discussion on post-fracture criteria. A general subroutine algorithm to handle plasticity based concrete constitutive relationships is also presented. The constitutive relationships as they apply to cracked concrete behavior were discussed. During the initial stages of this investigation, the development of ELASFEP, a finite element program, was undertaken. Program ELASFEP is a linear elastic dynamic finite element program capable of incremental predictive analysis. It utilizes the "Direct Method" in solving the dynamic governing equation. An overall description of NIEFE, the nonlinear implicit-explicit finite element code developed for this investigation, was presented. The code was capable of carrying out a nonlinear predictive analysis of concrete structure under general dynamic and static loading conditions. It utilized an implicit, explicit, or a mixed implicit-explicit direct integration technique. All the major steps involved in the code are presented in a general flow chart. In order to verify the developed computer code, three benchmark problems were solved. They were chosen because they all involve a wide range of response, and their behaviors are well documented both experimentally and analytically.